Medical Students React to Cadaveric Dissections - Usha Dubhashi1, Amarjit Singh2, Trinath T1, Siddharth Dubhashi1 (Recent Research in Science and Technology, 2011)
The medical student is under considerable stress as he is facing a professional course that needs total dedication and concentration. As enters the course, he goes through the anatomy curriculum, which involves interaction with cadavers and cadaveric material. This study analyses the reactions of students on their first exposure to the human cadaver. 300 students were included in the study. A proforma was designed with the objective of identifying specific patterns of attitudes and problems faced by the students on their first exposure to the human cadaver. Viewpoints regarding the need for pre-education sessions were also elicited. The positive feelings included a curiosity and interestÃ‚Â to learn about the structure of human body. Few were scared, some put off by the formalin fumes and few were hesitant to dissect the cadaver. Students also felt a sense of gratefulness to the people who donated their bodies for dissection. It was reported by some that negative feelings influenced their routine activities. Students felt the need to seek help from faculty in overcoming their anxiety. They felt that a pre-education session should be conducted before the formal dissection teaching begins which could instill a sense of respect into the minds of the students and eliminate the feeling of anxiety. A better teacher Ã¢â‚¬â€œ student interaction will go a long way in improving the attitude of students towards cadaveric dissection. This will offer a stable mental status for the fresh medicos to handle higher levels of stress in their clinical careers, thereby reducing the drop- out rates. Ã‚Â